Naevus striatus unguis. - Liddell, K. (BMJ Group, 1977)
Three patients presented with an asymptomatic longitudinal pigmented band in a nail. A junctional melanocytic naevus in the nail matrix was suspected; this was confirmed by histological examination in each case. Differential diagnosis and management are discussed, together with a review of the literature. Local excision is considered to be the treatment of choice.